Wireless Sensor Networks 6th European Conference, EWSN 2009 Cork, Ireland, February 11-13, 2009, Proceedings - Rödig, Utz; Sreenan, Cormac J. (Computer Communication Networks and Telecommunications, 2009)
This book constitutes the refereed proceedings of the 6th European Conference on Wireless Sensor Networks, EWSN 2009, held in Cork, Ireland, in Februar 2009. The 23 revised full papers presented were carefully reviewed and selected from 145 submissions. The papers are organized in topical sections on performance and quality of service, routing, coordination and synchronisation, data collection, security, as well as evaluation and management.